Efektifitas Herba Ciplukan (Physalis angulata L.) Sebagai Imunostimulan Kekebalan Unggas Setelah Uji Tantang Virus Newcastle Desease - Nurhasanah, N; Yellita, Yulia; Sabrina, S; Ananda, A (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This research aims to determine the effectiveness of ciplukan herb (Physalis angulata L) in extract and powder preparations as an immunostimulant against the immunity of broilers who have received vaccination and tested against the Newcastle disease virus. The materials used were 96 DOC with an average weight of 35-40 g, ciplukan herb from Luhak Nan Duo, the velogenic strain of Newcastle disease virus from Bvet Lampung, and the commercial vaccine ND Lasota. The study used a completely randomized design (CRD) with 8 treatments and 3 replications. The ciplukan herb was given for 3 days with concentrations: K(-) (without vaccine without ciplukan), K+ (vaccine only), E3 (ciplukan extract 0.35mg/10ml/head + vaccine), E2 (ciplukan extract 0.25mg/head 10ml/head + vaccine), E1 (0.15mg/10ml/head ciplukan extract + vaccine), S3 (17.5mg ciplukan powder/head + vaccine), S2 (12.5mg ciplukan powder/head + vaccine) and S1 (ciplukan powder 7.5mg/head + vaccine). The parameters observed in this study were antibody titer, morbidity, and mortality. The study showed that the administration of ciplukan herb positively affected low antibody titers through the efficiency of cellular defense mechanisms. This herb can also reduce chicken mortality and morbidity after challenge tests against the Newcastle disease virus.